Single-molecule insights into surface-mediated homochirality in hierarchical peptide assembly - Yumin Chen (Nature Portfolio, 2018)
Most chiral molecules and structures in living organisms exist as single enantiomers, but why? Here, the authors investigated surface-mediated homochirality on the single-molecule level and show that it can be triggered by the chirality unbalance of two adsorption configuration monomers.